Analisis Kompetensi Guru Menghadapi Era Revolusi Industri 4.0 - Zulkifli, Zulkifli (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
The industrial revolution 4.0 is characterized by cyber-physical systems, starting to touched the virtual of the world, in the form of human, machine and data connectivity, all of are which everywhere. This term is known as the Internet of Things (IoT). The 4.0 industrial revolution changed the way of life of various sectors of human life, one of them was education. One of the challenges in the field of education in the era of the industrial revolution 4.0 is the used of internet technology in learning which is part of 21st century learning. In 21st century learning, students are required to master their skills, knowledge, and abilities in the field of technology. In order to relized it, a teacher's competency and creativity is needed to face these challenges. Teachers who mastering the knowledge and ability to adapt in new technologies and global challenges can influence the skills and knowledge of students. The inprovement of teacher competency in facing the challenges of learning in the era of the industrial revolution is to attended activity forums such as MGMP, scientific forums, training (training), Higher Order Thinking Skills (HOTS) that can hone the skills of a teacher.